2010
DOI: 10.1080/03079450903490289
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of enteric viruses in breeder turkeys

Abstract: The present study was undertaken to detect and characterize enteric viruses (rotavirus, astrovirus, reovirus, and coronavirus) in breeder poults. Five turkey breeder flocks were selected. Faecal samples were collected from all flocks at 1 week of age and then every other week until the poults reached 9 weeks of age. The faecal samples were pooled in groups of five. Of the 193 pools (''samples'') tested by reverse transcriptionpolymerase chain reaction, 47.2%, 30.6%, and 10.4% samples were positive for astrovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 39 publications
9
49
0
8
Order By: Relevance
“…In the studies, rotaviruses were detected in flocks with enteric disease, but also in turkeys without any symptoms of the disease. This is in accordance with the results of previous studies, which demonstrated rotaviruses in both enteric and healthy birds (7,18).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the studies, rotaviruses were detected in flocks with enteric disease, but also in turkeys without any symptoms of the disease. This is in accordance with the results of previous studies, which demonstrated rotaviruses in both enteric and healthy birds (7,18).…”
Section: Discussionsupporting
confidence: 83%
“…The monitoring of enteric turkeys in Minnesota showed the presence of rotavirus in 48.3%-93% of tested flocks (6,8). In subsequent studies of these authors, the monitoring of five flocks of apparently healthy breeder turkeys over the period of nine weeks revealed that 30.6% of samples were rotavirus-positive and the virus was detected in 1-to 9-week-old, in both healthy and enteric turkeys (7). In Brazilian study, rotavirus infections were identified in 51.8% of surveyed turkey farms, and birds in most tested flocks were described as healthy (18).…”
Section: Discussionmentioning
confidence: 98%
“…The details of sample collection and processing have been described previously (Jindal et al, 2010b). Briefly, five faecal samples each were collected from eight different areas of a barn, at five different time points.…”
Section: Methodsmentioning
confidence: 99%
“…A genetically and antigenically distinct type of turkey astrovirus was then identified in 1996 (Turkey astrovirus type 2 [TAstV2]) by Koci et al (2000a). Since these first detections, enteritis in turkey has been increasingly associated with the presence of astroviruses (Cattoli et al, 2007;Pantin-Jackwood et al, 2007, 2008aDa Silva et al, 2008;Jindal et al, 2010a), although high astrovirus prevalence has also been reported in apparently healthy turkey flocks (PantinJackwood et al, 2007(PantinJackwood et al, , 2008aJindal et al, 2010b;Domanska-Blicharz et al, 2011). TAstV2 appears to be the most common among the identified turkey astroviruses, while TAstV1 and avian nephritis virus* an astrovirus first described as responsible for nephritis in chicken (Imada et al, 2000)*have only been detected sporadically in turkey flocks (Pantin-Jackwood et al, 2007, 2008aDomanska-Blicharz et al, 2011).…”
Section: Introductionmentioning
confidence: 99%